Mitochondrial genome of Isatis indigotica reveals repeat-mediated recombination and phylogenetic insights in Cruciferae - Yu, Shaoshuai; Qin, Meiling; Fleming, Emmanuel; Gong, Xun; Tang, Min (Frontiers in Plant Science, 2025)
Isatis indigotica is an important medicinal plant extensively used in traditional Chinese medicine for its antiviral and anti-inflammatory properties. While previous studies have elucidated its nuclear and plastid genomes, the mitochondrial genome (mitogenome) —critical for understanding organellar evolution, intracellular DNA transfer, and stress response mechanisms—has remained uncharacterized. Here, we present a complete de novo assembly and comprehensive analysis of the I. indigotica mitogenome, generated using high-fidelity long-read sequencing technologies. The circular mitogenome spans 260,864 bp and encodes 31 protein-coding genes, 21 transfer RNAs, and 3 ribosomal RNAs. Repetitive sequences constitute 12.3% of the genome, with large repeats mediating homologous recombination and generating alternative conformations. A total of 488 RNA editing sites were identified, predominantly of the cytidine-to-uridine (C-to-U) type, indicating extensive post-transcriptional modification. We also detected 36 regions homologous to the plastid genome, reflecting active inter-organellar DNA transfer. Codon usage analysis revealed a preference for A/U-ending codons, and Ka/Ks analysis suggested strong purifying selection in most mitochondrial genes. Phylogenomic analysis based on 24 conserved mitochondrial genes placed I. indigotica in close proximity to Brassica species, supporting its taxonomic placement within the Brassicaceae family and aligning with plastid-based phylogenies. This study provides the first complete mitogenome of I. indigotica, offering valuable insights into mitogenome architecture, RNA editing dynamics, and plastid–mitochondrial interactions, while contributing to broader evolutionary and genomic understanding of cruciferous medicinal plants.